Analysis of Sharia Accounting Principles in the Mandar Local Snack Business Model in Majene Regency - Wahyuni, Sri; Ilyas, Herlina; Ghalib, Abdul (Manunggal Halim Jaya, 2026)
This study aims to analyze how the principles of Sharia accounting are applied in the Mandar local snack industry in Majene Regency. Mandar's local snack industry is a rapidly growing community business sector and is an important part of the regional economy. However, the application of sharia accounting principles in business activities still faces various obstacles, including a lack of understanding of sharia concepts among business actors, unstandardized financial records, and limited access to sharia accounting literature. This study uses a qualitative, phenomenological approach to understand the direct experiences of business actors. Data were obtained through in-depth interviews, observations, and documentation, and analyzed interpretively to identify the main themes related to the application of sharia principles. The results of the study show that business actors have sought to implement the values of honesty, transparency, and fairness, but have not fully complied with Sharia accounting standards due to limited technical understanding and inadequate systematic recording. This research provides an empirical picture of the implementation of Sharia accounting in local small businesses. It offers recommendations to increase Sharia accounting literacy and support MSMEs. This finding is expected to be a reference for the development of policies to support sharia-based MSMEs.